TO THE QUESTION OF IMPROVING MEASURES TO PROVIDE PROCEEDINGS IN ADMINISTRATIVE DEFENSE CASES - Круглов, Валерій Олександрович; Бородін, Іван Лук'янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This paper discusses issues related to the problem of determining the measures of the law proceedings on administrative violations. The authors concluded that the procedural Executive Code of the Republic of Belarus on Administrative Offences, and in the Code of Ukraine on Administrative Offences as the measures of proceedings on administrative violations advisable to include the duty of an individual to appear in court challenge, body ( officer ) who is investigating or considering the case of an administrative offense, certification intoxicated, operating a vehicle ban , search and seizure .